Allow our children their childhood - Abd Razak, Dzulkifli (2009)
IT has been a month since the King of Pop died and the cause of his death is still under a shroud of controversy. But more of Michael Jackson, who died at the age of 50 on June 25, is coming to light. No less than his elder sister, La Toya, recently claimed that Michael was the "loneliest man in the world" with no real friends and isolated from his family at the time of his death. If this is so, it would be yet another piece of powerful evidence implying that wealth and fame are no guarantee of a higher quality of life, at least from the intangible viewpoint.